Persediaan Spare Part Menggunakan Reliability Centered Spares Dan inventory Analysis Di CV. selorejo Bantul - Aprilia Hardiyanti; Sodikin, Imam; Khasanah, Rahayu (Prodi Teknik Industri, Universitas AKPRIND Indonesia, 2022)
The results obtained from the RCS worksheet show that there is 1 unit of high critical category component, 10 units of medium critical category component and 4 units of low critical category component. Calculation of component requirements for the next 12 months using the Poisson process obtained the total requirement for 4 months of critical component spare parts to be able to meet 95% availability of v-belt mixers is 7 units (12 months = 21 units), hydraulic rubber requires 4 units (12 months=12 units), and vibrating v-belt system requires 2 units (12 months = 6 units). Order size and costs incurred for 4 months for 7 units of v-belt mixer component spare parts of IDR 569,500 (12 months = IDR 1,708,500), 4 units of hydraulic rubber components IDR 653,800 (12 months = IDR 1,961,400) and a v-belt system component of 2 units of IDR 103,300 (12 months = IDR 309,900). The total inventory cost for the 12 months that the company has to pay for the three critical component spare parts is IDR 3,979,800.